2017
DOI: 10.1177/1753425917727063
|View full text |Cite
|
Sign up to set email alerts
|

A novel nucleotide oligomerisation domain 2 mutation in a family with Blau syndrome: Phenotype and function

Abstract: Mutations in the nucleotide binding domain of the PRR, NOD2, are associated with the autoinflammatory diseases Blau syndrome and early-onset sarcoidosis. Current theories suggest that constitutive activation of the NOD2 pathway may be responsible for pathogenesis of these diseases. Here, we report the phenotype of a kindred with Blau syndrome caused by a novel NOD2 mutation (p.E383D). Signaling protein and cytokine expression were examined, and the results of these experiments challenge current theories of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Indeed, early studies in HEK cell lines transfected with NOD2 or Blau-variant NOD2 showed excessive NF-κB activity 50 , 51 at baseline levels and in response to MDP; thereby implicating over-activation of the canonical Nod2-signaling axis in Blau syndrome. However, more recent in vitro studies using PBMCs or monocytes 52 55 derived from patients with Blau syndrome showed reduced NF-κB activation and cytokines such as IL-1β in response to MDP, suggestive of a loss-of-function or “exhausted phenotype” in myeloid cells. We have also observed impaired MDP-signaling and NF-κB activation in macrophages derived from Blau patients, a cellular mechanism which was further dissected in Blau-mutant mice 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, early studies in HEK cell lines transfected with NOD2 or Blau-variant NOD2 showed excessive NF-κB activity 50 , 51 at baseline levels and in response to MDP; thereby implicating over-activation of the canonical Nod2-signaling axis in Blau syndrome. However, more recent in vitro studies using PBMCs or monocytes 52 55 derived from patients with Blau syndrome showed reduced NF-κB activation and cytokines such as IL-1β in response to MDP, suggestive of a loss-of-function or “exhausted phenotype” in myeloid cells. We have also observed impaired MDP-signaling and NF-κB activation in macrophages derived from Blau patients, a cellular mechanism which was further dissected in Blau-mutant mice 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The 38 patients with digestive system involvement comprised 15 men, 18 women, and five with unknown gender, with a median age at baseline evaluation of 20.3 years (range: 1.4–57). Of the 38 patients with digestive system involvement, 14 had hepatic granulomas proven by liver biopsy ( 5 , 7 , 11 , 16 , 20 27 ); five patients with hepatic granulomas had liver cirrhosis ( 21 , 23 , 24 , 26 , 27 ); 24 had enlarged liver and/or spleen ( 5 , 11 , 12 , 15 , 16 , 18 , 22 , 26 , 27 , 29 35 ); six had elevated liver enzymes including transaminase and cholestatic liver enzyme ( 21 24 , 26 , 27 ); five had gastrointestinal diseases including gastric ulcer, diverticulitis, Barrett's esophagus and small and large intestine granulomas ( 6 , 13 , 36 ); one had multiple splenic and hepatic lesions ( 28 ); and one had fatty liver ( 13 ) ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Defects within the nucleotide binding domain of NOD2 would act through receptor‐interacting protein kinase 2 and then the MAP kinase and NF‐κB pathways. However, gain‐of‐function of NOD2 in PGA was challenged in 2017 by Ong and colleagues, who found in peripheral blood monocytic cells obtained from affected family members with BS impaired production of IL‐6, TNFα, NF‐κB, IL‐1β, and INF‐γ. We note that INF‐γ1b (Actimmune) is used to treat malignant OPT before hematopoietic marrow cell transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…In PGA, granulomas are commonly identified in the associated dermatitis, but our patient's skin did not show this complication and therefore was not biopsied. Granulomas in PGA have been found in liver, kidney, a lymph node and tonsil, esophagus, synovial cyst, tendon, and elsewhere. In classic sarcoidosis, skeletal granulomas typically involve the marrow or cortex, and aberrant vitamin D and Ca metabolism occurs in up to 50% of patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation